Development of Portable Electronic Angle Listing Finder - Abdul Karim, Noor Hijratulsofia; Shaari, Norlida; Ibrahim, Badaruddin (Research and Innovation in Technical and Vocational Education and Training, 2024)
The welding industry in Malaysia is very extensive and this industry is very important in the field of manufacturing. This industry is categorized as a mechanical field that requires skills. The manufacture of fences and home iron grilles is mainly a welding service business that requires only skilled individuals. However, the tools used by them are not perfect and need a tool to improve the process of making and installing grills and furniture wood. However, this study was made based on the needs of welding workers from 5 companies. Researchers developed a tool to measure and support workpieces, the Portable Electronic Angle Index Finder. The materials used are mild steel and angle electronic magnets. Review from 5 experts, data analyzed using the SAW method for design selection and selection matrix method for product development requirements. In addition, this product has undergone experiments on the accuracy of the angle and timesaving of the product used to determine the effectiveness of the product. The results of the angle accuracy study show that 10º and 20º are less accurate but differ only slightly from 95% accuracy. Overall, all angles are accurate even though the materials are different. In terms of product usage savings, it is tested by taking the entire time before and after using the product. Experimental results show that making a grill can save time with an average of 3 hours and 15 minutes while the use of wood saves 1 hour. Therefore, this product has achieved all three objectives and can help the employees of the five companies to facilitate their work process.